RESTITUTION FOR UNJUST ENRICHMENT AND THE BREACH OF DEGROWTH OBLIGATIONS - Pereira, Leonardo Gomes (2024)
This paper aims to scrutinize unjust enrichment from the perspective of degrowth, a topic of profound importance today as it presents alternatives to uphold the constitutional principle of human dignity, ensuring equitable access to fundamental rights for all. It advocates for a paradigm shift in mindset and action, positioning degrowth as an integral duty linked to the fundamental obligation of protecting an ecologically balanced environment. In this context, maintaining production levels without adhering to the environmental limits set by relevant authorities is illegal. Profits derived from such acts thus constitute unjust enrichment and should be reallocated to those directly impacted, when identifiable, and to society at large, which endures the violation of its collective right to an ecologically balanced environment. The study utilizes an extensive interdisciplinary bibliographic approach, spanning from constitutional law through environmental and criminal law.